Synthesis, Spectral, and Fluorescence Studies of Fluorophenyl Methoxy Substituted Nickel Phthalocyanine Complex - Kilicarslan, Fatma Aytan (SPRINGER/PLENUM PUBLISHERS, 2023)
The synthesis, characterization, spectral, fluorescence properties of bis(4-fluorophenyl)-methoxy substituted nickel phthalocyanine were reported for the first time. The new compound has been characterized by elemental analysis, UV-Vis, FT-IR, H-1-NMR and mass spectra. The aggregation behaviour of this compound was investigated in the different solvent and concentrations of in CHCl3. Phthalocyanine complex did not show any aggregations. The fluorescent properties of the compound in five different solvents such as CHCl3 CH2Cl2 THF, DMF, DMSO were explained. Phthalocyanine complex gave the highest fluorescence quantum yield in CHCl3 and the lowest fluorescence quantum yield in DMSO.
Keywords: Phthalocyanines; Fluorescence; Aggregation; ZINC PHTHALOCYANINES; PHOTOCHEMISTRY; PHOTOPHYSICS; POLLUTANTS; PHENOXY; Biochemistry & Molecular Biology; Chemistry